Improvement of thermal performance of double skin roof with forced ventilation - Gao, Wen (2014)
Reduction of electric consumption helps to slow down the effect of green-house and provides a better living environment for the next generation. In Singapore the cooling system takes up the majority of the electricity consumption. There is an increasing trend of using mechanical ventilation system to secure thermal comfort. Double-skin roof greatly reduces the heat transfers of both conduction and convection from the roof to the ceiling of the building. Previous works mainly focused on optimal air gap and the inclined angle for the better thermal performance of the double-skin roof.